2016
DOI: 10.1021/acs.jpclett.6b01931
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Deep UV Spectra of Interfacial Aqueous Iodide

Abstract: The behavior of ions at aqueous interfaces influences vital processes in many fields but has long remained a subject of controversy. Over the past decade, counterintuitive surface concentration enhancement of several ions in aqueous solution has been demonstrated via nonlinear laser spectroscopy and mass spectrometry. While the evidence for significant ion enhancement at the air-water interface is convincing, the mechanism remains incompletely understood. Toward this end, we present the full broadband DUV-SFG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 28 publications
(43 reference statements)
0
40
0
Order By: Relevance
“…This repulsion was originally explained by classical electrostatic theory 47 and supported by surface tension measurements which showed that the surface tension increased as a function of salt concentration. 48,49 More recently, molecular dynamics simulations, 50,51 surface specific second-order nonlinear optical experiments, [52][53][54] and XPS measurements 33,39 have predicted and observed the enhancement of certain simple ions at the air/water interface. These models have shown that weakly hydrated, charge-diffuse ions are generally enhanced at the air/water interface.…”
Section: Fig 4 Measured X-ray Photoemission Spectra Of 50:50mentioning
confidence: 99%
“…This repulsion was originally explained by classical electrostatic theory 47 and supported by surface tension measurements which showed that the surface tension increased as a function of salt concentration. 48,49 More recently, molecular dynamics simulations, 50,51 surface specific second-order nonlinear optical experiments, [52][53][54] and XPS measurements 33,39 have predicted and observed the enhancement of certain simple ions at the air/water interface. These models have shown that weakly hydrated, charge-diffuse ions are generally enhanced at the air/water interface.…”
Section: Fig 4 Measured X-ray Photoemission Spectra Of 50:50mentioning
confidence: 99%
“…One fundamental nonlinear probe is second harmonic generation (SHG), a second-order process which combines two photons of the same energy to generate a single photon with twice the energy [8]. At infrared, visible, and ultraviolet wavelengths, second-order nonlinear spectroscopies have become important tools in surface science, as symmetry considerations, within the dipole approximation, constrain signal generation to regions lacking centrosymmetry, such as surfaces and interfaces [9][10][11][12]. In contrast, at hard X-ray wavelengths, second harmonic and sum frequency generation (SFG) have been observed in centrosymmetric materials with a non-uniform electron density and are essentially bulk probes [1,2].…”
mentioning
confidence: 99%
“…Additionally, as the pulses remains fully coherent, it should be possible to combine this technique with lens-less coherent imaging techniques with a resolution not limited by aberration [31]. Such a technique would require either an energy-sensitive nondispersive detector or the generation of a signal that is spatially separated from the input pulses, as has been achieved previously with non-collinear input laser pulses, such as in optical SFG [9][10][11][12]. If radiation damage concerns can be mitigated, the spectral sensitivity demonstrated here would enable experiments which can both spectroscopically and spatially resolve nanoparticles.…”
mentioning
confidence: 99%
“…One fundamental nonlinear probe is second harmonic generation (SHG), a secondorder process which combines two photons of the same energy to generate a single photon with twice the energy [8]. At infrared, visible, and ultraviolet wavelengths, secondorder nonlinear spectroscopies have become important tools in surface science, as symmetry considerations within the dipole approximation constrain signal generation to regions lacking centrosymmetry, such as surfaces and interfaces [9][10][11][12]. In contrast, at hard x-ray wavelengths, second harmonic and sum frequency generation (SFG) have been observed in centrosymmetric materials with a nonuniform electron density and are essentially bulk probes [1,2].…”
mentioning
confidence: 99%
“…Additionally, as the pulses remain fully coherent, it should be possible to combine this technique with lensless coherent imaging techniques with a resolution not limited by aberration [41]. Such a technique would require either an energy-sensitive nondispersive detector or the generation of a signal that is spatially separated from the input pulses, as has been achieved previously with noncollinear input laser pulses, such as in optical SFG [9][10][11][12]. If radiation damage concerns can be mitigated, the spectral sensitivity demonstrated here would enable experiments which can both spectroscopically and spatially resolve nanoparticles.…”
mentioning
confidence: 99%